A kind of high-efficiency wear-resistant ceramic coating and preparation method thereof

Through optimized preparation process and modification technology, metal oxide, nitride and carbide composite materials are modified with silane coupling agent, blended with shell powder and sintered to form high-efficiency wear-resistant ceramic coatings, which solves the problem of insufficient wear resistance and high temperature stability of traditional coatings in complex industrial environments, and significantly improves the overall performance of the coatings.

CN119286291BActive Publication Date: 2025-03-25JIANGSU FAYIN NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411609933.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-03-25
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

Traditional wear-resistant ceramic coatings are difficult to meet the needs of high wear resistance and high temperature stability in complex industrial environments, especially shell powder is prone to agglomeration after micronization, affecting the dispersion and performance of the coating.

Method used

Through optimized preparation process and modification technology, metal oxide, nitride and carbide composite materials are modified with silane coupling agent, blended with shell powder and sintered to form a highly efficient wear-resistant ceramic coating.

Benefits of technology

It significantly improves the wear resistance, high temperature stability and overall performance of the coating, extends the service life of the coating, and shows stronger durability in complex industrial environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005130678850000101
    Figure BDA0005130678850000101
  • Figure BDA0005130678850000111
    Figure BDA0005130678850000111
Patent Text Reader

Abstract

The present invention relates to a kind of efficient wear-resistant ceramic coating and its preparation method, belong to the technical field of coating material preparation, specifically comprising the following steps: using metal oxide and nitride compound, after silane coupling agent modification, mixing with carbide, preparing wear-resistant reinforcement material. Then this material is mixed with shell powder and sintered, ball milled and sieved after cooling. Finally, the treated material is mixed with resin in a ratio of 1g: (0.2-0.3) g, stirred at 400-600rpm for 5-6 hours, and an efficient wear-resistant ceramic coating is obtained. The present application provides a kind of efficient wear-resistant ceramic coating and its preparation method to meet the high requirements of complex industrial environment for coating performance. By optimizing the preparation process and modification technology, the wear resistance, high temperature stability and overall performance of the coating are improved, and new technical paths and solutions are provided for the development of the coating industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of coating material preparation, and more specifically, to a high-efficiency wear-resistant ceramic coating and a preparation method thereof. Background Art

[0002] As a high-performance inorganic coating, wear-resistant ceramic coatings are widely used in pipelines, industrial facilities and other fields. However, the wear resistance and high-temperature stability of traditional wear-resistant ceramic coatings still need to be improved, especially in complex and changing industrial environments, where the overall performance and durability of the coatings face challenges.

[0003] As a natural resource with a wide range of sources and low costs, shell materials have attracted extensive attention and been applied in the coating industry in recent years. After micronization, shell powder can significantly improve the dispersibility and compatibility of coatings and enhance the overall performance of coatings. However, shell powder is prone to agglomeration after micronization, which limits its use in coatings and affects the final performance of coatings. Agglomeration causes the shell powder in the coating to be unable to be evenly distributed, reducing the wear resistance and stability of the coating. Therefore, how to effectively reduce the agglomeration of shell powder and improve its dispersibility has become a key issue in improving the performance of coatings.

[0004] Based on the above statements, the present application provides a high-efficiency wear-resistant ceramic coating and a preparation method thereof. Summary of the invention

[0005] In order to solve the problems raised in the background technology, this application provides a highly efficient wear-resistant ceramic coating and a preparation method thereof to meet the high requirements of coating performance in complex industrial environments. By optimizing the preparation process and modification technology, the wear resistance, high temperature stability and overall performance of the coating are improved, providing a new technical path and solution for the development of the coating industry.

[0006] A method for preparing a high-efficiency wear-resistant ceramic coating comprises the following preparation steps:

[0007] S1. Compounding metal oxides and nitrides to obtain a compound material, modifying the compound material with a silane coupling agent, and then mixing the compound material with a carbide to prepare a wear-resistant reinforcement material;

[0008] S2. Mix the wear-resistant reinforcing material and shell powder, then sinter the system, and then cool it to room temperature, ball mill and sieve it, and then mix it with the resin material, seal and stir the system to obtain a high-efficiency wear-resistant ceramic coating.

[0009] Furthermore, a method for preparing a highly efficient wear-resistant ceramic coating comprises the following preparation steps:

[0010] S1. Compounding metal oxides and nitrides to obtain a compound material, modifying the compound material with a silane coupling agent, and then mixing the compound material with a carbide to prepare a wear-resistant reinforcement material;

[0011] S2. Mix the wear-resistant reinforcing material and shell powder, then sinter the system, cool it to room temperature, ball mill it for 2-5 hours, pass it through a 300-350 mesh sieve, and then mix it with the resin material at a mass ratio of 1g:(0.2-0.3)g. Stir the system in a sealed manner at a rate of 400-600rpm for 5-6 hours to obtain a high-efficiency wear-resistant ceramic coating.

[0012] Furthermore, in step S1, the metal oxide is at least one of Al2O3, TiO2, ZrO2 and Cr2O3.

[0013] Furthermore, in step S1, the nitride is at least one of Si3N4, TiN, BN and AlN.

[0014] Furthermore, the specific operation of modifying the composite material using a silane coupling agent is as follows:

[0015] The silane coupling agent is dissolved in a solvent, stirred evenly at room temperature, and then ammonia monohydrate is added to the system, the system temperature is increased to 60-80°C, and stirred to obtain a silane coupling agent solution; the composite material is added to the silane coupling agent solution, mixed at 60-80°C for 1-3 hours, and then filtered and washed with a solvent.

[0016] Furthermore, the specific operation of modifying the composite material using a silane coupling agent is as follows:

[0017] The silane coupling agent is dissolved in methyl ethyl ketone solvent, stirred evenly at room temperature, and then ammonia monohydrate is added to the system, the system temperature is increased to 60-80°C, and stirred at a rate of 30-90rpm for 0.5-1 hour to obtain a silane coupling agent solution; the composite material is added to the silane coupling agent solution according to a mass volume ratio of 1g:5-10mL, mixed at a rate of 300-500rpm at 60-80°C for 1-3 hours, and then filtered and washed with a solvent for 3-5 times.

[0018] In the above reaction process, the silane coupling agent is hydrolyzed to generate methoxy groups, which then react with hydroxyl groups on the composite material to modify the organic silane on the composite material, thereby obtaining a modified composite material.

[0019] Furthermore, the mass ratio of the silane coupling agent to ammonia monohydrate is (1-1.5):2.

[0020] Furthermore, in step S1, the carbide is tungsten carbide (hereinafter referred to as WC).

[0021] Furthermore, in step S1, the mass ratio of metal oxide, nitride and carbide is (30-35):(25-35):(10-20).

[0022] Furthermore, in step S2, the specific operation of the sintering process is:

[0023] The system was heated to 550-600° C. at a heating rate of 10-20° C. / min in an air atmosphere, the sintering time was set to 1-3 hours, and then kept warm for 10-20 minutes.

[0024] Furthermore, in step S1, the mass ratio of the wear-resistant reinforcing material to the shell powder is (2-3):(0.5-1).

[0025] In summary, this application has the following beneficial effects:

[0026] 1. In the technical solution of the present invention, WC, nitride and metal oxide are compounded to enhance ceramic wear-resistant coatings. Nitride and metal oxide powders have high hardness, high wear resistance and good lubricity, can effectively reduce friction and wear, and can be compounded with WC to further enhance the wear resistance of the coating. At the same time, WC, nitride and metal oxide together form an efficient heat conduction network in the coating. The close combination and mutual penetration between these materials enable heat to be quickly transferred inside the coating, thereby improving the thermal stability of the coating.

[0027] 2. In the technical solution of the present invention, a silane coupling agent is used to modify the metal oxide and nitride components. The silane coupling agent can form a protective film on the surface of the metal oxide and nitride, optimize the interface structure, reduce friction and scratches during wear, and thus improve the wear resistance of the coating. In addition, the silane coupling agent can effectively prevent the oxidation and decomposition of the metal oxide and nitride, thereby extending the service life of the coating. The chemical bonding layer formed on the surface of the metal oxide and nitride can also improve the thermal stability of the material.

[0028] 3. In the technical solution of the present invention, WC is blended with shell powder, and then sintered at 550-600°C together with metal oxide and nitride components modified by silane coupling agent, and the obtained material is used to enhance ceramic wear-resistant coatings. Shell powder contains a large amount of calcite components, which can be used to enhance the coating after micronization treatment, which can greatly improve the wear resistance. The tungsten oxide and calcium oxide products obtained by high-temperature decomposition of WC and shell powder that have not been modified by silane coupling agent during the sintering treatment undergo phase change at high temperature, which can greatly improve the dispersion effect of the shell material in the coating after micronization. At the same time, the silane coupling agent can also promote the close bonding between WC, shell powder and metal oxides and nitrides, and improve the overall thermal stability of the coating. DETAILED DESCRIPTION

[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] The silane coupling agent involved in the specific implementation manner of the present application is KH550, and the resin material used is a mixture of vinyl epoxy resin and 650 curing agent in a mass ratio of 6:1; the shell powder used comes from clams.

[0031] Example 1

[0032] A method for preparing a high-efficiency wear-resistant ceramic coating comprises the following preparation steps:

[0033] S1. Compounding metal oxides and nitrides to obtain a compound material, modifying the compound material with a silane coupling agent, and then mixing the compound material with a carbide to prepare a wear-resistant reinforcement material;

[0034] Wherein, the metal oxide is CrO2; the nitride is BN; the carbide is WC;

[0035] Among them, the mass ratio of metal oxide, nitride and carbide is 30:25:10;

[0036] Among them, the specific operation of modifying the compound material using a silane coupling agent is:

[0037] 1 g of silane coupling agent was dissolved in 100 mL of methyl ethyl ketone solvent, and after being stirred evenly at room temperature, 2 g of ammonia monohydrate was added to the system, the system temperature was raised to 60° C., and stirred at 30 rpm for 0.5 hours to obtain a silane coupling agent solution; the composite material was added to the silane coupling agent solution at a mass volume ratio of 1 g:5 mL, mixed at 60° C. at 300 rpm for 1 hour, and then filtered and washed with a solvent for 3 times;

[0038] S2, the wear-resistant reinforcing material and the shell powder are mixed, and then the system is sintered, and then cooled to room temperature, ball milled for 2 hours, passed through a 300-mesh sieve, and then mixed with a resin material at a mass ratio of 1g:0.2g, and the system is sealed and stirred at a rate of 400rpm for 5 hours to obtain a high-efficiency wear-resistant ceramic coating;

[0039] Among them, the mass ratio of wear-resistant reinforcing material and shell powder is 2:0.5.

[0040] Among them, the specific operation of sintering treatment is:

[0041] The system was heated to 550° C. at a heating rate of 10° C. / min in an air atmosphere, the sintering time was set to 1 hour, and then kept at the temperature for 10 minutes.

[0042] Example 2

[0043] A method for preparing a high-efficiency wear-resistant ceramic coating comprises the following preparation steps:

[0044] S1. Compounding metal oxides and nitrides to obtain a compound material, modifying the compound material with a silane coupling agent, and then mixing the compound material with a carbide to prepare a wear-resistant reinforcement material;

[0045] Wherein, the metal oxide is CrO2; the nitride is BN; the carbide is WC;

[0046] Among them, the mass ratio of metal oxide, nitride and carbide is 33:30:15;

[0047] Among them, the specific operation of modifying the compound material using a silane coupling agent is:

[0048] 1.2 g of silane coupling agent was dissolved in 100 mL of methyl ethyl ketone solvent, and after being stirred evenly at room temperature, 2 g of ammonia monohydrate was added to the system, the system temperature was raised to 70° C., and stirred at 60 rpm for 1 hour to obtain a silane coupling agent solution; the composite material was added to the silane coupling agent solution at a mass volume ratio of 1 g:8 mL, mixed at 70° C. at 400 rpm for 2 hours, and then filtered and washed with a solvent for 4 times;

[0049] S2, the wear-resistant reinforcing material and shell powder are mixed, and then the system is sintered, and then cooled to room temperature, ball milled for 3.5 hours, passed through a 300-mesh sieve, and then mixed with a resin material at a mass ratio of 1g:0.25g, and the system is sealed and stirred at a rate of 500rpm for 6 hours to obtain a high-efficiency wear-resistant ceramic coating;

[0050] Among them, the mass ratio of wear-resistant reinforcing material and shell powder is 2.5:0.8.

[0051] Among them, the specific operation of sintering treatment is:

[0052] The system was heated to 580° C. at a heating rate of 10° C. / min in an air atmosphere, the sintering time was set to 2 hours, and then kept at the temperature for 15 minutes.

[0053] Example 3

[0054] A method for preparing a high-efficiency wear-resistant ceramic coating comprises the following preparation steps:

[0055] S1. Compounding metal oxides and nitrides to obtain a compound material, modifying the compound material with a silane coupling agent, and then mixing the compound material with a carbide to prepare a wear-resistant reinforcement material;

[0056] Wherein, the metal oxide is Al2O3; the nitride is TiN; the carbide is WC;

[0057] Among them, the mass ratio of metal oxide, nitride and carbide is 35:35:20;

[0058] Among them, the specific operation of modifying the compound material using a silane coupling agent is:

[0059] 1.5 g of silane coupling agent was dissolved in 100 mL of methyl ethyl ketone solvent, and after being stirred evenly at room temperature, 2 g of ammonia monohydrate was added to the system, the system temperature was raised to 80° C., and stirred at 90 rpm for 1 hour to obtain a silane coupling agent solution; the composite material was added to the silane coupling agent solution at a mass volume ratio of 1 g:10 mL, mixed at 80° C. at 500 rpm for 3 hours, and then filtered and washed with a solvent for 5 times;

[0060] S2, mixing the wear-resistant reinforcing material and the shell powder, then sintering the system, then cooling to room temperature, ball milling for 5 hours, passing through a 350-mesh sieve, and then mixing with the resin material at a mass ratio of 1g:0.3g, and sealing and stirring the system at a speed of 600rpm for 6 hours to obtain a high-efficiency wear-resistant ceramic coating;

[0061] Among them, the mass ratio of wear-resistant reinforcing material and shell powder is 3:0.5.

[0062] Among them, the specific operation of sintering treatment is:

[0063] The system was heated to 600° C. at a heating rate of 20° C. / min in an air atmosphere, the sintering time was set to 3 hours, and then kept at the temperature for 20 minutes.

[0064] Example 4

[0065] The difference between this comparative example and Example 3 is that in step S1, the metal oxide is CrO2; the nitride is BN; the carbide is WC;

[0066] Comparative Example 1

[0067] The difference between this comparative example and Example 1 is that in step S1, the wear-resistant reinforcement material is prepared by the following steps:

[0068] The metal oxide is modified by using a silane coupling agent and then mixed with a carbide to prepare a wear-resistant reinforcement material;

[0069] Among them, the mass ratio of metal oxide to carbide is 55:10.

[0070] Comparative Example 2

[0071] The difference between this comparative example and Example 1 is that in step S1, the wear-resistant reinforcement material is prepared by the following steps:

[0072] The nitride is modified by using a silane coupling agent and then mixed with a carbide to prepare a wear-resistant reinforcement material;

[0073] Among them, the mass ratio of nitride to carbide is 55:10.

[0074] Comparative Example 3

[0075] The difference between this comparative example and Example 1 is that in this comparative example, in step S1, the wear-resistant reinforcement material is prepared by the following steps:

[0076] Compounding metal oxides and nitrides to obtain a compound material, and modifying the compound material with a silane coupling agent to prepare a wear-resistant reinforcement material;

[0077] Among them, the mass ratio of metal oxide to nitride is 30:25.

[0078] Comparative Example 4

[0079] The difference between this comparative example and Example 1 is that the step S1 of this comparative example is:

[0080] S1. Compounding metal oxides, nitrides and carbides to obtain a compound material, modifying the compound material with a silane coupling agent to prepare a wear-resistant reinforcement material, the specific operation is as follows:

[0081] 1 g of silane coupling agent was dissolved in 100 mL of methyl ethyl ketone solvent, and after being stirred evenly at room temperature, 2 g of ammonia monohydrate was added to the system, the system temperature was raised to 60° C., and stirred at 30 rpm for 0.5 hours to obtain a silane coupling agent solution; the composite material was added to the silane coupling agent solution at a mass volume ratio of 1 g:5 mL, mixed at 60° C. at 300 rpm for 1 hour, and then filtered and washed with a solvent for 3 times;

[0082] Wherein, the metal oxide is CrO2; the nitride is BN; the carbide is WC;

[0083] Among them, the mass ratio of metal oxide, nitride and carbide is 30:25:10.

[0084] Comparative Example 5

[0085] The difference between this comparative example and Example 1 is that in the sintering process in step S2, an inert atmosphere is used instead of air for sintering.

[0086] Comparative Example 6

[0087] The difference between this comparative example and Example 1 is that no sintering treatment is performed in step S2.

[0088] Performance Testing

[0089] The high-efficiency wear-resistant ceramic coatings prepared in Examples 1-4 and Comparative Examples 1-6 of the present application were coated on 50 cm*50 cm clay green body samples with a coating thickness of 0.2 mm, and then dried at 60°C.

[0090] Wear resistance test: Then, referring to the method described in GB / T 1768-2006, the wear resistance tester was used to test the wear resistance of the samples prepared in different groups.

[0091] Hardness test: Refer to the method described in GB / T 6739-2006 to test the hardness of the coating.

[0092] Thermal stability test: Use a muffle furnace and a temperature controller to heat treat the samples prepared in different groups. Set the heating rate to 10°C / minute, raise the temperature to 300°C, keep it warm for 2 hours, and then naturally cool it to room temperature. Then observe the coating surface and evaluate the coating performance to determine the thermal stability of samples in different groups. The evaluation criteria are as follows:

[0093] Grade A: The coating has no cracking or peeling after heat treatment, the surface is flat and smooth, and there are no cracks or peeling visible to the naked eye.

[0094] Grade B: The coating shows slight cracking or falling off after heat treatment, but the cracks are few and small, and the falling off area is less than 5% of the total area.

[0095] Grade C: The coating shows obvious cracking and falling off after heat treatment. The cracks are numerous and widely distributed, and the falling off area accounts for 5% to 20% of the total area.

[0096] Grade D: The coating almost completely falls off or cracks severely after heat treatment, and the falling area accounts for more than 20% of the total area, and the coating loses its protective effect.

[0097] The specific performance test results are shown in Table 1:

[0098] Table 1

[0099]

[0100]

[0101] From the results shown in Table 1 above, it can be seen that the comprehensive performance of the ceramic coatings prepared in Examples 1-4 of the present application is significantly better than that of the samples prepared in Comparative Examples 1-6, that is, within the technical solution defined in the present application, the comprehensive performance of the ceramic coatings prepared is excellent. From the results of the wear resistance test and the hardness test, it can be seen that the combination of carbides, metal oxides, WC and shell powder can form a good wear-resistant system and improve the wear resistance of the material. After heat treatment at a specific temperature, the effect of components such as shell powder and WC on improving the wear resistance of the material can be better exerted. From the thermal stability results, it can be seen that the samples in Examples 1-4 have a very strong bonding force between the coating and the substrate, can withstand thermal stress changes in a high temperature environment, and maintain the integrity and stability of the coating.

[0102] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0103] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing a highly efficient wear-resistant ceramic coating, characterized in that: The method comprises the following preparation steps: S1. Compounding metal oxides and nitrides to obtain a compound material, modifying the compound material with a silane coupling agent, and then mixing the compound material with a carbide to prepare a wear-resistant reinforcement material; S2, mixing the wear-resistant reinforcing material and shell powder, then sintering the system, then cooling to room temperature, ball milling and sieving, then mixing with the resin material, sealing and stirring the system, and obtaining a high-efficiency wear-resistant ceramic coating; The specific operation of the sintering process is as follows: The system was heated to 550-600° C. at a heating rate of 10-20° C. / min in an air atmosphere, the sintering time was set to 1-3 hours, and then kept warm for 10-20 minutes.

2. The method for preparing a high-efficiency wear-resistant ceramic coating according to claim 1, characterized in that: In step S1, the metal oxide is at least one of Al2O3, TiO2, ZrO2 and Cr2O3.

3. The method for preparing a high-efficiency wear-resistant ceramic coating according to claim 1, characterized in that: In step S1, the nitride is at least one of Si3N4, TiN, BN and AlN.

4. The method for preparing a high-efficiency wear-resistant ceramic coating according to claim 1, characterized in that: The specific operation of modifying the compound material using a silane coupling agent is as follows: The silane coupling agent is dissolved in a solvent, stirred evenly at room temperature, and then ammonia monohydrate is added to the system, the system temperature is increased to 60-80°C, and stirred to obtain a silane coupling agent solution; the composite material is added to the silane coupling agent solution, mixed at 60-80°C for 1-3 hours, and then filtered and washed with a solvent.

5. The method for preparing a high-efficiency wear-resistant ceramic coating according to claim 4, characterized in that: The mass ratio of the silane coupling agent to the ammonia monohydrate is 1-1.5:

2.

6. The method for preparing a high-efficiency wear-resistant ceramic coating according to claim 1, characterized in that: In step S1, the mass ratio of metal oxide, nitride and carbide is 30-35:25-35:10-20.

7. The method for preparing a high-efficiency wear-resistant ceramic coating according to claim 1, characterized in that: In step S1, the carbide is tungsten carbide.

8. The method for preparing a high-efficiency wear-resistant ceramic coating according to claim 1, characterized in that: In step S1, the mass ratio of the wear-resistant reinforcing material to the shell powder is 2-3:0.5-1.

9. A ceramic coating obtained by the method for preparing a high-efficiency wear-resistant ceramic coating as claimed in any one of claims 1 to 8.

Citation Information

Patent Citations

  • Ceramic coating with high-temperature resistance and wear resistance and preparation method of ceramic coating

    CN106007678A

  • High-hardness and scratch-resistant instrument and apparatus shell coating

    CN108727977A